ANALISIS AMANAT DALAM PUISI “DOA” KARYA CHAIRIL ANWAR - Wanti Kurniasih; Ika Mustika; Aditya Permana (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Poetry is a literary work in the form of a meaningful expression of human thoughts and feelings. Analysis of the message in poetry is very necessary, to find out more about its meaning. This research can be useful for readers or writers in building literary works and increasing the reader's ability to analyze a poem. This study aims to determine the mandate contained in the poem entitled DOA by Chairul Anwar. To find out this mandate, researchers used a qualitative descriptive method. The data were collected by analyzing DOA's poetry and then described it in words. The benefit of this research is to make it easier for the reader to understand the meaning contained in the DOA poem by Chairil Anwar. Sources are obtained from class VIII SMP / MTs Indonesian language textbooks. Based on the results of the research, it can be concluded that the mandate contained in the DOA poem is that we as servants should humbly ask ourselves so that all our desires are fulfilled, whether in any condition, anywhere.